(untitled) - Perrin, Nicholas (Great Britian, 2007)
This text tells the story of the Gospel of Thomas from its discovery to its current reception among academics and in more popular circles. It provides a clear, comprehensive, non-technical guide through the scholarly maze of issues surrounding the Coptic text.
Keywords: Gospel of Thomas (Coptic Gospel) -- Criticism, interpretation, etc